Redox cycling metals: Pedaling their roles in metabolism and their use in the development of novel therapeutics - Kalinowski, D.; Stefani, C.; Toyokuni, S.; Ganz, T.; Anderson, G.; Subramaniam, N.; Trinder, D.; Olynyk, John; Chua, A.; Jansson, P.; Sahni, S.; Lane, D.; et al. (2016)
Essential metals, such as iron and copper, play a critical role in a plethora of cellular processes including cell growth and proliferation. However, concomitantly, excess of these metal ions in the body can have deleterious effects due to their ability to generate cytotoxic reactive oxygen species (ROS). Thus, the human body has evolved a very well-orchestrated metabolic system that keeps tight control on the levels of these metal ions. Considering their very high proliferation rate, cancer cells require a high abundance of these metals compared to their normal counterparts. Interestingly, new anti-cancer agents that take advantage of the sensitivity of cancer cells to metal sequestration and their susceptibility to ROS have been developed. These ligands can avidly bind metal ions to form redox active metal complexes, which lead to generation of cytotoxic ROS. Furthermore, these agents also act as potent metastasis suppressors due to their ability to up-regulate the metastasis suppressor gene, N-myc downstream regulated gene 1. This review discusses the importance of iron and copper in the metabolism and progression of cancer, how they can be exploited to target tumors and the clinical translation of novel anti-cancer chemotherapeutics.